Differential Expression of miRNAs in Trichloroethene-Mediated Inflammatory/Autoimmune Response and Its Modulation by Sulforaphane: Delineating the Role of miRNA-21 and miRNA-690 - Banerjee, Nivedita; Wang, Hui; Wang, Gangduo; Boor, Paul J.; Khan, M. Firoze (Frontiers in Immunology, 2022)
Trichloroethene (TCE), an occupational and ubiquitous environmental contaminant, is associated with the induction of autoimmune diseases (ADs). Although oxidative stress plays a major role in TCE-mediated autoimmunity, the underlying molecular mechanisms still need to be delineated. Altered non-coding RNAs, including the expression of microRNAs (miRNA’s) can influence target genes, especially related to apoptosis and inflammation, and contribute to ADs. Therefore, the objective of this study was to delineate the contribution of miRNAs in TCE-mediated inflammatory and autoimmune response. To achieve this, we treated female MRL+/+ mice with TCE (10 mmol/kg in corn oil, ip, every fourth day) with/without antioxidant sulforaphane (SFN; 8 mg/kg in corn oil, ip, every other day) for 6 weeks. Using miRNA microarray, 293 miRNAs were analyzed which included 35 miRNAs that were relevant to inflammation and ADs. Among those 35 miRNAs, 8 were modulated by TCE and/or TCE+SFN exposure. TCE treatment led to increased expression of 3 miRNAs and also decreased expression of 3 miRNAs. Interestingly, among the 35 differentially expressed miRNAs, antioxidant SFN modulated the expression of 6 miRNAs. Based on the microarray findings, we subsequently focused on two miRNAs (miRNA-21 and miRNA-690) which are known to be involved in inflammation and autoimmune response. The increases in miRNA-21 and miR-690 (observed using miRNA microarray) were further validated by RT-PCR, and the TCE-mediated increases in miR-21 and miR-690 were ameliorated by SFN treatment. Modulating miR-21 and miR-690 by respective inhibitors or mimics suppressed the expression of NF-κB (p65) and IL-12 in RAW 264.7 cells. Our findings suggest a contributory role of miR-21 and miR-690 in TCE- and its metabolite DCAC-mediated inflammation and autoimmune response and support that antioxidant SFN could be a potential therapeutic candidate for inflammatory and ADs.